The Aerobic and Cognitive Exercise Study (ACES) for Community-Dwelling Older Adults With or At-Risk for Mild Cognitive Impairment (MCI): Neuropsychological, Neurobiological and Neuroimaging Outcomes of a Randomized Clinical Trial - Anderson-Hanley, Cay; Barcelos, Nicole M.; Zimmerman, Earl A.; Gillen, Robert W.; Dunnam, Mina; Cohen, Brian D.; Yerokhin, Vadim; Miller, Kenneth E.; Hayes, David J.; Arciero, Paul J.; Maloney, Molly; Kramer, Arthur F. (Frontiers in Aging Neuroscience, 2018)
Prior research has found that cognitive benefits of physical exercise and brain health in older adults may be enhanced when mental exercise is interactive simultaneously, as in exergaming. It is unclear whether the cognitive benefit can be maximized by increasing the degree of mental challenge during exercise. This randomized clinical trial (RCT), the Aerobic and Cognitive Exercise Study (ACES) sought to replicate and extend prior findings of added cognitive benefit from exergaming to those with or at risk for mild cognitive impairment (MCI). ACES compares the effects of six months of an exer-tour (virtual reality bike rides) with the effects of a more effortful exer-score (pedaling through a videogame to score points). Fourteen community-dwelling older adults meeting screening criteria for MCI (sMCI) were adherent to their assigned exercise for six months. The primary outcome was executive function, while secondary outcomes included memory and everyday cognitive function. Exer-tour and exer-score yielded significant moderate effects on executive function (Stroop A/C; d’s = .51 and .47); there was no significant interaction effect. However, after three months the exer-tour revealed a significant and moderate effect, while exer-score showed little impact, as did a game-only condition. Both exer-tour and exer-score conditions also resulted in significant improvements in verbal memory. Effects appear to generalize to self-reported everyday cognitive function. Pilot data, including salivary biomarkers and structural MRI, were gathered at baseline and six months; exercise dose was associated with increased BDNF as well as increased grey matter volume in the PFC and ACC. Improvement in memory was associated with an increase in the DLPFC. Improved executive function was associated with increased expression of exosomal miRNA-9. Interactive physical and cognitive exercise (both high and low mental challenge) yielded similarly significant cognitive benefit for adherent sMCI exercisers over six months. A larger RCT is needed to confirm these findings. Further innovation and clinical trial data are needed to develop accessible, yet engaging and effective interventions to combat cognitive decline for the growing MCI population.